Uppföljning av plantering på nedlagd åkermark i Skåne 1991-1996 - Blomquist, Anders (SLU/Southern Swedish Forest Research Centre, 2006)
The study was performed for the Swedish Regional Forestry Board in Södra Götaland. The study examines broadleaf plantations on former farmland that were planted between 1991 and 1996 with subsidy payments for conversion of farmland into forest. In particular, the study reviews forests planted in 1991-92 and 1994-96.